Pembunuhan karena Mahar (Dowry Killing) dan Pembunuhan demi Kehormatan (Honor Killing): Batas Doktrinal dan Desain Pembuktian - Zul Khaidir Kadir (CV. ITTC INDONESIA, 2026)
This study aims to formulate an operational boundary between dowry killing and honor killing by identifying their underlying driving mechanisms, explaining the consequences of these differences for mens rea and evidentiary indicators, and assessing whether special offence regimes and evidentiary presumptions enhance accountability or instead displace proof with category-based judgments. The research employs normative legal methodology with a conceptual approach, mapping coercive mechanisms onto offence elements and evidentiary pathways, while critically evaluating the design of special offences and judicial presumptions. The findings indicate that dowry-related killing operates through economic coercion based on recurring material demands, coercive family bargaining, and escalating harassment, making transaction trails, demand communications, and patterned cruelty central to proof. Honor-based homicide, by contrast, operates through reputation restoration oriented toward social recognition, where proof turns on shame-related language, reputational threats, markers of social legitimation, and the collective dimension of decision-making. The study further shows that special offences and presumptions may strengthen accountability but risk over-inclusion and under-inclusion when applied without evidence-based classification gates.